2021
DOI: 10.1002/tqem.21778
|View full text |Cite
|
Sign up to set email alerts
|

Technical–economic potential of agrivoltaic for the production of clean energy and industrial cassava in the Colombian intertropical zone

Abstract: A dispute is being created in the countries between the use of land for photovoltaic generation purposes and agriculture to satisfy food demand. Therefore, the agrivoltaic concept is presented as a dual-purpose land-use solution. A technical-economic analysis is carried out to install photovoltaic systems elevated to a considerable height from the ground, and under them, industrial cassava is grown. A mixed-integer linear optimization model is developed to store energy in a battery bank, reduce the energy abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is accomplished according to the nature of the country's features, research objective, and opinions of experts. It is worth mentioning that the seasonal precipitation and potential evapotranspiration values, refer to the period April to September included, as also considered in the studies from Grusson et al (2021) for irrigation of spring cereal, potatoes, and grass ley in Sweden. Morel et al (2021) reported common sowing and harvest dates from barley, maize, oats, and spring wheat varying between the beginning of May to the begin of October.…”
Section: Methodsmentioning
confidence: 99%
“…This is accomplished according to the nature of the country's features, research objective, and opinions of experts. It is worth mentioning that the seasonal precipitation and potential evapotranspiration values, refer to the period April to September included, as also considered in the studies from Grusson et al (2021) for irrigation of spring cereal, potatoes, and grass ley in Sweden. Morel et al (2021) reported common sowing and harvest dates from barley, maize, oats, and spring wheat varying between the beginning of May to the begin of October.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the agricultural yields of a-Si and CdTe plants are better than mc-Si plants. The average simple payback period for the agrivoltaic system was 5 and 8 years [40][41][42]. Agrivoltaics can reduce the variable behavior of apple trees, demonstrating the importance of conducting years of research [43].…”
Section: Review Of the Literaturementioning
confidence: 99%